Development of a Velcro Glove Model for Catching Baseballs in Fourth-Grade Elementary School - Annisa Tri Heriani; Eka Fitri Novitasari; Mastri Juniarto (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This study seeks to create a prototype of Velcro-coated gloves to enhance the effectiveness of baseball catching instruction in fourth-grade elementary schools. Materials and methods. This study improves the baseball catching skills of fourth-grade students by using a glove with a Velcro coating. This study utilizes the ADDIE technique, including of five discrete stages: analysis, design, model creation, implementation, and evaluation. The development of the glove model involves an iterative process of creating and testing various materials and shapes of gloves to determine the most suitable design that matches the size and characteristics of grade IV pupils. Result. A proficient glove design should enhance the capacity to catch baseballs while ensuring the comfort and safety of kids. The validity test result of 0.7 indicates that it is considered valid, while the reliability value of 0.6 falls into the high category. The validation results for the development of the Velcro glove media, as assessed by 13 validators, indicate a strong agreement with an average percentage of 89.3%. Conclusion. Enhancing pupils' proficiency in catching baseballs is expected to increase their engagement in physical exercise.